COVID-19-associated coagulopathy: review of current recommendations for diagnosis, treatment and prevention - K. V. Lobastov; I. V. Schastlivtsev; O. Ya. Porembskaya; O. V. Dzenina; A. B. Bargandzhiya; S. N. Tsaplin (Амбулаторная хирургия)
The coronavirus infection COVID-19 is a highly contagious disease caused by the SARS-CoV-2 virus. Specific prothrombotic changes of the hemostasis system in COVID-19 are associated with increased incidence of venous thromboembolic complications. The article is a literature review on the diagnosis, treatment and prevention of coagulopathy and venous thromboembolic complications associated with COVID-19. 11 studies evaluating the frequency of registration of venous thromboembolic complications and 11 clinical recommendations on correction of coagulopathy published before May 22, 2020 have been studied. The frequency of venous thromboembolic complications was unexpectedly high: 8–13% in the general ward and 9–18% in the intensive care unit against the background of preventive measures. Preventive doses of anticoagulants, low-molecular weight heparins or unfractionated heparin are indicated to all hospitalized patients. Prolonged prophylaxis after discharge from hospital can be recommended for those at high risk of venous thromboembolic complications and low risk of bleeding. An increase in D-dimer may be considered as an indication for instrumental detection of venous thromboembolic complications. If there is a suspicion of venous thromboembolic complications, anticoagulant therapy at therapeutic doses can be started before the diagnosis is confirmed: during inpatient treatment preference should be given to low-molecular heparin or unfractionated heparin, after discharge from hospital it is recommended to transfer to direct oral anticoagulants for a period of at least 3 months. Routine prevention of venous thromboembolic complications in ambulatory patients is not recommended.